Задача размещения заказов и алгоритм ее решения - Бойко, В.В.; Кузьменко, В.Н. (Теорія оптимальних рішень, 2005)
The paper considers an order allocation problem with a discounts objective function and investigates its features. An algorithm solving this problem is proposed. Such an algorithm includes the ralgorithm for obtaining lower estimations. Additional constrains are generated for initial problem, and algorithm operation is accelerated. The results of the computational experiments are given.